The Realization of Communication Accommodation Strategies between Teacher and Students at Easy Learning English Course - Arum istiqomah; Frimadhona Safri; Katharina Rustipa (English Education Journal, 2024)
It is a challenge for English teacher in an English course to be able to accommodate in teaching so that students are not confused with what the teacher explains during the communication. This research aims to investigate the kinds of communication accommodation strategies realized in teacher-student interaction in Easy Learning English Course. This study used qualitative research design in the classroom interaction analysis. The instrument applied was strategies checklist to find and interpret the strategies realized. This study found that based on the analysis in the interaction between teacher and students in Easy Learning English Course, the communication accommodation strategies used were approximation strategy, interpretability strategy, discourse management strategy and interpersonal control strategy. The strategies used in the interaction enable the teacher to accommodate in the communication with the students in the classroom. This study shows that the communication accommodation strategies realized in the teacher student interaction in Easy learning English course are 26 times approximation strategy, 38 times interpretability strategy, 351 discourse management strategy and 14 times interpersonal control strategy in Conclusion, Discourse management strategy is more dominant than approximation strategy, interpretability strategy, and interpersonal control strategy.